Electronic grade and flexible semiconductor film employing oriented attachment of colloidal ligand-free PbS and PbSe nanocrystals at room temperature1. Issue 20 (28th May 2015) - Shanker, G. Shiva; Swarnkar, Abhishek; Chatterjee, Arindom; Chakraborty, S.; Phukan, Manabjyoti; Parveen, Naziya; Biswas, Kanishka; Nag, Angshuman
<x xml:space="preserve">Abstract</x> Ligand-free colloidal PbS and PbSe nanocrystals undergo sintering at room temperature leading to the fabrication of flexible and electronic grade semiconductor films.